2010
DOI: 10.1590/s1678-91992010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical comparison of venoms from young Colombian Crotalus durissus cumanensis and their parents

Abstract: ABSTRACT:Crotalus durissus cumanensis, a rattlesnake endemic to Colombia and Venezuela, is considered one of the most lethal snake species in Latin America. The aim of the present study was to compare the protein content and biological activity of the venom obtained from eight specimens of C. durissus cumanensis, namely two adults from different localities of Colombia and six offspring born in captivity. Protein profiles of crude venoms were analyzed by SDS-PAGE and RP-HPLC, and biological activities were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…Previously, Cespedes et al reported an LD 50 for the venom of C. d. cumanensis of 47 µg/kg for females and 41 µg/kg for juveniles. These results are consistent with those described in this study; however, the males were shown to be less lethal [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Cespedes et al reported an LD 50 for the venom of C. d. cumanensis of 47 µg/kg for females and 41 µg/kg for juveniles. These results are consistent with those described in this study; however, the males were shown to be less lethal [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pre-incubation of venoms with SVSPs inhibitor (PMSF) completely inhibited the coagulant activity of venoms, indicating that this activity is mediated solely by SVSPs. Similar results has been reported in species such as C. durissus cumanensis [18] and C. d. terrificus [75] where venoms from neonate or juvenile snakes had MCD-P lower (more coagulant) than venoms of adult snakes. These results suggest that fibrinogenases are responsible for activity in C. m. nigrescens venoms breaking both α- and β-chains of fibrinogen, while TL-SVSPs would be responsible of the activity in venoms with affinity only for the α-chain of fibrinogen.…”
Section: Discussionsupporting
confidence: 87%
“…In general, more toxic and procoagulant venoms have been detected in newborn or juvenile snakes compared to adults [16,17,18,19,20,21,22]. These ontogenetic differences in biological activities of venoms could be reflected in different clinical manifestations in people bitten by newborn, juvenile or adult snakes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results of the present study, we can suggest that CDCmV must contain several different toxins that could act either individually or synergistically. It is important to highlight that the ontogenic and paedomorphic variations in venom composition of Crotalus durissus subspecies, including C. d. cumanensis, are considerable and may cause important variations in the biological effects of individual venoms (40,41).…”
Section: Discussionmentioning
confidence: 99%